Study on the Variation Pattern and Influencing Factors of Poisson’s Ratio of Bamboo - Lu, Haojie; Lian, Hongyang; Xu, Jiayu; Ma, Niuniu; Zhou, Zhezhe; Song, Yuanpu; Yu, Youming; Zhang, Xiaochun (Frontiers in Materials, 2022)
As a natural polymer material, bamboo is regard as a super material with lightweight but excellent mechanical properties. With the increasing application of bamboo in structure, high-strength composite materials, bridges, musical instruments and damping materials, the study of Poisson's ratio is of great significance to the structural design and stability of these materials. In this work, Poisson’s ratio of bamboo for different age, growth height and bamboo wall radial direction was determined by electrical measurement. The relationships between intrinsic factors (density, chemical composition, crystallinity and microfibril angle) and Poisson’s ratio were also analyzed. The results showed that Poisson’s ratio of bamboo for different age and location were range from 0.180 to 0.334, decreased with the increasing bamboo age, growth height and the radial direction from the outer layer to the inner layer. While the peaks values of Poisson’ ratio were obtained at bamboo for 2 years old, lower growth height and near bamboo outer layer. Furthermore, the Poisson’s ratio had positive correlation with the increasing density, cellulose content and MFA, but negative correlation with lignin content. There is no direct relationship between the crystallinity and Poisson's ratio, but it affects the axial and transverse deformation of bamboo, which can be used as an indirect index to judge Poisson's ratio.